In Vitro Photodynamic Inactivation Effects of Ru(II) Complexes on Clinical Methicillin‐resistant Staphylococcus aureus Planktonic and Biofilm Cultures. (5th December 2014) - Wang, Yucheng; Zhou, Qianxiong; Wang, Ying; Ren, Jie; Zhao, Hongyou; Wu, Sumin; Yang, Jiyong; Zhen, Jie; Luo, Yanping; Wang, Xuesong; Gu, Ying
Abstract Photosensitizers (PSs) combined with light are able to generate antimicrobial effects. Ru(II) complexes have been recognized as a novel class of PSs. In this study, we investigated the effectiveness of photodynamic inactivation (PDI) mediated by three Ru(II) polypyridine complexes, 1–3, against four isolates of clinical methicillin‐resistant Staphylococcus aureus (MRSA‐1, MRSA‐2, MRSA‐3 and MRSA‐4). In PDI of a planktonic culture of MRSA‐1, compound 3 showed the highest efficacy, likely owing to its advantageous light absorption, 1O2 quantum yield and bacterial cellular binding. The PDI efficacy of 3 was further evaluated against all other strains and MRSA‐1 biofilms. At appropriate PS concentrations, viability reduction of 100% or 96.83% was observed in planktonic or biofilm forms of MRSA, respectively. The mechanisms of action were investigated using negative staining transmission electron microscopy (TEM), confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). It was demonstrated that PDI of planktonic bacteria was achieved primarily through damage to the cell envelope. Biofilms were eliminated through both the destruction of their structure and inactivation of the individual bacterial cells. In conclusion, Ru(II) complexes, especially 3, are potential candidates for the effective photodynamic control of MRSA infections.